Evolutionary interactions between Drosophila melanogaster and its parasitoid Asobara tabida. - Green, D; Kraaijeveld, A; Godfray, H (2000)
Drosophila melanogaster is attacked by parasitoids that develop internally in the larva. They can defend themselves by a cellular immune response (host resistance), although this can be disabled by parasitoid countermeasures (parasitoid virulence). D. melanogaster and its parasitoids are an excellent system in which to study coevolution experimentally. We designed an experiment to compare changes in resistance and virulence in replicate populations of flies and parasitoids maintained together for approximately 10 fly (five parasitoid) generations. The experiment had three treatments each with three replicates: (A) no parasitoids (B) outbred parasitoids (C) partially inbred parasitoids. Host resistance increased in treatments B and C but there was no difference between these treatments. Parasitoid virulence appeared not to change during the experiment. Host larvae in treatments B and C fed at lower rates than those in A, evidence of a trade-off between resistance and larval competitive ability. We found no evidence for local adaptation, as hosts from the different replicates of treatment C performed no differently against parasitoids from the same and other replicates. Also, we found no evidence for the evolution of behavioural traits in the host that could lead to lower probabilities of being attacked. Comparing the evolution of host resistance in these seminatural settings with that in artificial selection experiments provides insight into how the conflicting selection pressures on host resistance interact.